Landwirtschaft und klimatische Trends im zentralen Yarlong Tsangpo -Tal, Tibet - Thomas, Axel; Shenbin, Chen (ERDKUNDE, 2002)
The Yarlong Tsangpo valley in southern Tibet is the centre of Tibetan farming. About 75% of the area is cultivated with local barley cultivars with some additional spring and winter wheat. With the exception of the Xigaze basin, cultivation is limited by seasonal flooding to higher ground on terraces, debris fans and small upslope areas in the valley. Generally favourable thermal and solar conditions in the subtropical high-altitude valley at elevations between 3500 - 3900 m are offset by low precipitation and high evapotranspiration rates. Previous temperature-based estimates of evapotranspiration rates underestimate the actual conditions considerably; annual Penman-Monteith evapotranspiration totals are estimated at 1194 und 1364 mm for Lhasa and Xigaze. Based on long-term water balance calculations (1954 - 1990), the seasonal water demand of barley and wheat is estimated at 460 - 730 mm (580 - 770 mm) and 530 - 840 mm (660 - 920 mm) at Lhasa (and Xigaze, resp.). Mean total plant-available water during the growing season amounted to only 54 - 59% and 44 - 49% of the seasonal water demand (wheat and barley, resp.) at Lhasa and Xigaze, resp. and decreased by 12% and 4 - 8% during that period. Estimated water balance data therefore point to increasingly arid conditions in the region. A shift towards cultivating more drought-tolerant barley cultivars instead of wheat, and raising the effectiveness of irrigation systems are possible counter measures.